Współpraca transgraniczna i międzyregionalna pomiędzy Polską a Niemcami = Cross-border and interregional cooperation between Poland and Germany - Madajczyk, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents how the cross-border cooperation between Poland and German Democratic Republic (GDR) developed. It describes the complicated relations in which Polish - GDR contacts were on the one hand "fraternal" relations of the two socialist countries, but on the other they were a part of Polish fears of "the Germans" and Polish politics based on the dogma of the threat from Federal Republic of Germany (FRG). The visits of German tourists, both from GDR and FRG, were sentimental journeys of the Germans expelled from Polish territory.
Keywords: stosunki polsko-niemieckie; współpraca polsko-niemiecka; współpraca regionalna